Physical exercise, inflammatory process and adaptive condition: an overview. DOI: 10.5007/1980-0037.2011v13n4p320 - Fernando Oliveira Catanho da Silva; Denise Vaz Macedo (Universidade Federal de Santa Catarina, 2011)
Physical exercise induces inflammation, a physiological response that is part of immune system activity and promotes tissue remodeling after exercise overload. The activation of the inflammatory process is local and systemic and is mediated by different cells and secreted compounds. The objective is to reestablish organ homeostasis after a single bout of exercise or after several exercise sessions. The acute-phase response involves the combined actions of activated leukocytes, cytokines, acute-phase proteins, hormones, and other signaling molecules that control the response to an exercise session and guide the adaptations resulting from training. This review provides an overview of the inflammatory process related to exercise and literature data regarding markers of inflammation in response to different experimental protocols. The results obtained indicate distinct inflammatory responses to acute and chronic exercise. In general, acute exercise induces a proinflammatory response characterized by transient leukocytosis (neutrophilia, monocytosis, and lymphocytosis), followed by a partial cellular immunosuppressive state. An increase in serum concentrations of creatine kinase, C-reactive protein and cell adhesion molecules is also observed, in addition to an increased secretion of cortisol and cytokines. In contrast, chronic exercise results in a local and systemic anti-inflammatory response that promotes tissue adaptation and protects the organism against the development of chronic inflammatory diseases and against the effects of non-functional overtraining, a condition in which a systemic and chronic proinflammatory and pro-oxidant state seems to prevail.